Inside the Crisis : An Empirical Analysis of Banking Systems in Distress - Gupta, Poonam (IMF Working Papers; Working Paper ;, 2000)
Using aggregate and bank level data for several countries, the paper studies what happens to the banking system in the aftermath of a banking crisis. Contemporary crises are not accompanied by declines in aggregate bank deposits, and credit does not fall relative to output, although the growth of both deposits and credit slows down substantially. Output recovery begins in the second year after the crisis and is not led by a resumption in credit growth. Banks, including the stronger ones, reallocate their asset portfolio away from loans.